The Constitutional Limit of Searching people Caught in the Act. A comparative Analytical Study between Egyptian and Palestinian Legislation - Abd.Elaal, Ayman Nasr (Journal of Economic, Administrative and Legal Sciences, 2022)
Legislation at its various levels is keen to protect personal freedom, and based on that, this study was conducted to demonstrate the success of the Palestinian legislator in this, especially since he included in the Basic Law definitive texts that protect it and prohibit its infringement except according to specific legal controls, and no exceptions were made to them. On the other hand, the text of the Law Palestinian penal procedures for arresting and searching persons in flagrante delicto of committing crimes without this having a basis or exception in the Basic Law. The Egyptian texts of the Code of Criminal Procedures in these cases, and this became clear by following the analytical and comparative approach between the Egyptian and Palestinian legislations to show the contradiction between the texts of the Palestinian Basic Law and the Code of Criminal Procedures.
Keywords: red flag; search; arrest; persons; constitutionality